Bibliometric guide to photographs of male participants in early exercise and physical medicine research - James L. Nuzzo (Journal of Men's Health)
The history of exercise science research has undergone relatively little examination, and exercise science students receive little education about the field’s history. Photographs are tools that lecturers and writers can use to educate audiences about history. Yet, no resource exists that tells educators where they can find photographs of individuals participating in early studies about exercise or related topics (e.g., physical education, physical medicine). Here, the aim was to identify papers published before 1980 that contain photographs of boys and men participating in studies about exercise or related topics, aggregate the papers into a bibliometric list, and describe the photographs. The current research focused on boys and men to give male experiences and contributions their own space for acknowledgement. The entire digital archives of Journal of Applied Physiology (1948–1979), Medicine and Science in Sports (1969–1979) and Research Quarterly (1930–1979) were searched. Papers published in other journals (e.g., Physical Therapy) were identified via searches of personal digital files from previous historical work. A total of 304 papers were identified. Of these papers, 44.1% were published in Research Quarterly. The earliest paper was published in 1894. The papers included 733 photographs of male participants (46 boys, 475 men), with some males appearing in multiple photographs. Of the 304 papers, 49.0% and 27.3% were classified as research primarily on neuromuscular and cardiorespiratory outcomes, respectively. Educators can use the bibliometric list to identify photographs to include in lectures and writings about the history of exercise science and the contributions made by male research participants.